2016
DOI: 10.1016/j.carbpol.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and screening of N-acyl thiolated chitosans for antibacterial applications

Abstract: Low-molecular weight chitosan-thioglycolic acid has shown significant antibacterial properties against different microorganisms. In order to explore the potential and structure-activity relationships of newly synthesized alkyl thiomers, chitosan has been functionalized with a series of thio-acids with increasing alkyl chain length. All thiomers were characterized with special emphasis on the determination of their degree of deacetylation and substitution, as well as on their molecular weight and amount of thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…1 H‐NMR of PIII displayed new additional peaks at 2.48–2.65 ppm due to the protons of the methyl group (SCH 2 CH 3 ) that interfered with the other methyl group of PHB and 2.76–2.81 ppm due to the C H 2 SC H 2 protons (f and g, Figure ) . The sulfur content of PIII was 0.91% (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…1 H‐NMR of PIII displayed new additional peaks at 2.48–2.65 ppm due to the protons of the methyl group (SCH 2 CH 3 ) that interfered with the other methyl group of PHB and 2.76–2.81 ppm due to the C H 2 SC H 2 protons (f and g, Figure ) . The sulfur content of PIII was 0.91% (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…They began to be explored in 1999 [10], and have since been used in multiple biomedical and pharmaceutical applications due to the close interest in their study among the research community [11][12][13]. These applications are connected with the presence of their thiol groups and their capability of conducting thiol-disulfide exchange reactions and oxidizing to disulfide bridges: from soft-tissue engineering [14] as biomaterial support for cartilage repair [15] and 3D bioscaffolds for cell culture [16,17] to antibacterial activity [18][19][20][21]. They are also prominent candidates for the formulation of controlled delivery carriers of APIs, whether for topical use [22], as dry powder inhalers [23], or in oral administration [24], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the significant effect of antimicrobial biopolymers and chitosan itself to enhance the wound healing process through preventing the wound infections that result in tissue maceration 23 , 25 27 . It has been reported that chitosan modified diisocyanate (DIMC) 28 , O-quaternary ammonium N-acyl thiourea chitosan 29 , chitosan-thioglycolic acid 30 , kanamycin-chitosan nanoparticles 31 , crosslinked chitosan 32 and O-amine functionalized chitosan 33 exhibited better antibacterial activity degrees against Escherichia coli , Staphyloccocus aureus and other microorganisms. Likewise, chitosan Schiff base derivatives are considered one of the best choices for increasing antimicrobial activity of chitosan, since carbonyl groups of aldehyde or ketone can efficiently couple with NH 2 groups of chitosan to form the corresponding chitosan Schiff base with imine characteristic group (-RC=N-) 34 .…”
Section: Introductionmentioning
confidence: 99%